- KOMPETENSI PEDAGOGIK DALAM PRAKTIK MANAJEMEN SUMBER DAYA MANUSIA : KAJIAN LITERATUR: KOMPETENSI PEDAGOGIK DALAM PRAKTIK MANAJEMEN SUMBER DAYA MANUSIA : KAJIAN LITERATUR - Arsyad, Arsyad; Budiwati, Neti; Hibrida, Anas Romzy (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2025)
Pedagogic competence plays an increasingly important role in Human Resource Management (HRM) practices, especially in the context of employee training and development. Although this concept is more often associated with formal education, its application in the world of work can make a significant contribution to the development of individuals and organizations. This article aims to examine the concept and application of pedagogic competencies in HRM, as well as the challenges and opportunities that exist in its application. Based on a literature review, this article finds that good pedagogic competence can increase training effectiveness, encourage continuous learning, and create a collaborative and innovative work culture. In addition, this article also discusses recommendations for the development of pedagogic competencies in the context of HRM.